2023
DOI: 10.3390/cryst13020282
|View full text |Cite
|
Sign up to set email alerts
|

Study on Electrochemical Properties of Carbon Submicron Fibers Loaded with Cobalt-Ferro Alloy and Compounds

Abstract: In this work, carbon submicron fiber composites loaded with a cobalt-ferric alloy and cobalt-ferric binary metal compounds were prepared by electrospinning and high temperature annealing using cobalt-ferric acetone and ferric acetone as precursors and polyacrylonitrile as a carbon source. The phase transformation mechanism of the carbon submicron fiber-supported Co-Fe bimetallic compound during high temperature annealing was investigated. The electrochemical properties of the carbon submicron fiber-supported C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This experiment conducted simulation experiments on analog circuits using the Iris dataset as experimental data. A stable power supply voltage was input to the analog circuit, and the complete circuit was subjected to static scanning observation and classification [21,22]. Specifically, the highest voltage output value of Iris flowers is represented as the classification and recognition results of the experiment.…”
Section: Simulation Results Of Analog Circuits Based On Nvfmumentioning
confidence: 99%
“…This experiment conducted simulation experiments on analog circuits using the Iris dataset as experimental data. A stable power supply voltage was input to the analog circuit, and the complete circuit was subjected to static scanning observation and classification [21,22]. Specifically, the highest voltage output value of Iris flowers is represented as the classification and recognition results of the experiment.…”
Section: Simulation Results Of Analog Circuits Based On Nvfmumentioning
confidence: 99%
“…To optimize the computational performance and resource allocation capacity of a fog computing wireless access network, Jo et al proposed to construct a computational task offloading and resource allocation strategy, validated the effectiveness of the proposed optimization strategy, and found that this strategy significantly improved the system processing efficiency and resource allocation compared with the traditional processing methods [ 14 ]. In the transportation system, the logistics path-planning performance is insufficient and there is the problem of long computation times, so Yu et al proposed the deep reinforcement learning mechanism to optimize the logistics path-planning model to verify the model’s effectiveness, and found that the computation time of the model compared with the traditional model was significantly shortened, and the phase of the computation time in the path planning was better [ 15 ]. To further improve the precision and accuracy of fluid flow control, Rabault et al proposed to apply deep reinforcement learning techniques to the training of the flow control to construct an active control model of the flow and validated the effectiveness of this model, which was found to successfully stabilize the vortex channel and reduce the resistance by approximately 8%, opening the way for the execution of active flow control [ 16 , 17 , 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among them, green visibility mainly refers to the actual proportion of green vegetation perceived by human vision, which characterizes human activity space rather than urban surface space and focuses more on the restoration of the actual vitality space of the landscape. Higher green visibility can relax people physically and mentally and enhance life satisfaction [15][16][17][18]. The corresponding expression is shown in Equation (5).…”
Section: Deeplab V3+ Model Analysis and Quantitative Measurement Fram...mentioning
confidence: 99%